Peningkatan Investasi Daerah melalui Kemudahan Perizinan di Kota Tangerang Selatan Berdasarkan Perda Nomor 7 Tahun 2013 Tentang Penyelenggaraan Reklame - Fitrianto, Sigit; Saefullah; Setyowati, Retno Kus (IAI Nasional Laa Roiba Bogor, 2025)
The city that contributes to investment in order to improve the national economy is South Tangerang due to the ease of licensing in the city of South Tangerang based on Regional Regulation Number 7 of 2013 concerning the Implementation of Advertisements. Problem: How can ease of advertising licensing increase regional investment in South Tangerang City? What are the obstacles to increasing regional investment through ease of licensing in South Tangerang City based on Regional Regulation Number 7 of 2013 concerning the Implementation of Advertisements? Normative legal research research methods. In conclusion, regional investment in the context of facilitating licensing in the city of South Tangerang based on Regional Regulation Number 7 of 2013 concerning the Implementation of Advertisements is one of the policy focuses for improving the investment climate in Indonesia. The development of One Stop Integrated Services (PTSP) has become the government's agenda for registration and establishment of business sectors. The licensing bureaucracy is one of the obstacles to the development of the world of business in Tangierang Sielatan City. Many of the licensing processes that are currently available have various aspects of process, problems, non-transparency, unplanned timing and high costs that must be paid.